Stevens Johnson syndrome and toxic epidermal necrolysis induced by HAART prophylaxis in the National Hospital Almanzor Aguinaga Asenjo, Lambayeque, Perú - Soto Cáceres, Victor A. (2007)
Stevens-Johnson syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) are acute inﬂammatory reactions due to hypersensitivity and inmunological responses that involves skin and mucous membranes. Adverse effects of antiretroviral drugs in a 25 year old male who received Highly Active Anti-Retroviral Therapy as prophylaxis were diagnosed. He had exanthema that progresse to SJS and advanced to TEN. He was in an Intensive Care Unit, but he had several complications and died with sepsis.